2021
DOI: 10.1186/s13613-021-00936-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prognostic factors between bacteraemic and non-bacteraemic critically ill immunocompetent patients in community-acquired severe pneumococcal pneumonia: a STREPTOGENE sub-study

Abstract: Background The presence of bacteraemia in pneumococcal pneumonia in critically ill patients does not appear to be a strong independent prognostic factor in the existing literature. However, there may be a specific pattern of factors associated with mortality for ICU patients with bacteraemic pneumococcal community-acquired pneumonia (CAP). We aimed to compare the factors associated with mortality, according to the presence of bacteraemia or not on admission, for patients hospitalised in intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…This study found that a higher RAPID score was significantly linked to overall mortality in patients with complicated pleural infections, consistent with previous research [ 9 , 24 , 28 ]. On the other hand, the presence of bacteremia did not seem to have a substantial impact on mortality in these patients, consistent with other recent studies suggesting that bacteremia was not associated with an increased risk of mortality in patients with pneumococcal pneumonia, including those admitted to intensive care unit [ 27 , 29 ]. The relatively lower diagnostic and prognostic value of blood culture testing implies limited usefulness in patients with pleural infection.…”
Section: Discussionsupporting
confidence: 89%
“…This study found that a higher RAPID score was significantly linked to overall mortality in patients with complicated pleural infections, consistent with previous research [ 9 , 24 , 28 ]. On the other hand, the presence of bacteremia did not seem to have a substantial impact on mortality in these patients, consistent with other recent studies suggesting that bacteremia was not associated with an increased risk of mortality in patients with pneumococcal pneumonia, including those admitted to intensive care unit [ 27 , 29 ]. The relatively lower diagnostic and prognostic value of blood culture testing implies limited usefulness in patients with pleural infection.…”
Section: Discussionsupporting
confidence: 89%
“…10,11 Approximately 40% of patients admitted to ICU for pneumococcal community-acquired pneumonia are bacteremic, 26,27 and one recent study of ICU patients showed that the blood culture status had no influence on mortality outcomes. 28 The rate of bacteremia-positive sepsis in our ED cohort is 8%, approximately half of the 17% found in a study set in an ICU and three general wards combined, 5 and substantially lower than the 51% found in another ICU-only study. 6 As patients transferred to ICU have already had a deteriorating condition identified, this highlights the important role of the ED in triage and investigation of the diverse patient groups presenting with suspected sepsis.…”
Section: Nonbacteremic Sepsis Cases With Positive Urine Cultures (Bc−...mentioning
confidence: 54%
“…Severe respiratory infections are more commonly culture‐negative, with studies finding an association between CNSS and higher rates of respiratory infection 10,11 . Approximately 40% of patients admitted to ICU for pneumococcal community‑acquired pneumonia are bacteremic, 26,27 and one recent study of ICU patients showed that the blood culture status had no influence on mortality outcomes 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies did not report the proportion of lumbar puncture and therefore meningitis in patients admitted to ICU for pneumococcal pneumonia [ 7 , 9 , 11 ], a mortality rate from neurological cause from 5 to 7% was reported [ 9 , 11 , 22 ], suggesting that some of these patients may have undiagnosed meningitis. In this regard, Figueiredo and colleagues found that in patients admitted for bacterial meningitis, mainly pneumococcal meningitis, pneumonia was a frequent coexisting infection on admission [ 23 ].…”
Section: Discussionmentioning
confidence: 99%